Variations in Rodent Models of Type 1 Diabetes: Islet Morphology - Lesya Novikova; Irina V. Smirnova; Sonia Rawal; Abby L. Dotson; Stephen H. Benedict; Lisa Stehno-Bittel (Journal of Diabetes Research)
Type 1 diabetes (T1D) is characterized by hyperglycemia due to lost or damaged islet insulin-producing β-cells. Rodent models of T1D result in hyperglycemia, but with different forms of islet deterioration. This study focused on 1 toxin-induced and 2 autoimmune rodent models of T1D: BioBreeding Diabetes Resistant rats, nonobese diabetic mice, and Dark Agouti rats treated with streptozotocin. Immunochemistry was used to evaluate the insulin levels in the β-cells, cell composition, and insulitis. T1D caused complete or significant loss of β-cells in all animal models, while increasing numbers of α-cells. Lymphocytic infiltration was noted in and around islets early in the progression of autoimmune diabetes. The loss of lymphocytic infiltration coincided with the absence of β-cells. In all models, the remaining α- and δ-cells regrouped by relocating to the islet center. The resulting islets were smaller in size and irregularly shaped. Insulin injections subsequent to induction of toxin-induced diabetes significantly preserved β-cells and islet morphology. Diabetes in animal models is anatomically heterogeneous and involves important changes in numbers and location of the remaining α- and δ-cells. Comparisons with human pancreatic sections from healthy and diabetic donors showed similar morphological changes to the diabetic BBDR rat model.